Combination of mTOR and EGFR targeting in an orthotopic xenograft model of head and neck cancer. (24th November 2015) - Bozec, Alexandre; Ebran, Nathalie; Radosevic‐Robin, Nina; Sudaka, Anne; Monteverde, Martino; Toussan, Nicolas; Etienne‐Grimaldi, Marie‐Christine; Nigro, Cristiana Lo; Merlano, Marco; Penault‐Llorca, Frédérique; Milano, Gérard
Abstract : Objectives/Hypothesis: Recent preclinical and clinical studies on head and neck squamous cell carcinoma (HNSCC) revealed synergistic effects when combining anti‐EGFR agents with conventional chemotherapeutic drugs. Activation of the PI3‐kinase/AKT/mTOR signaling pathway has been identified as an important mechanism implicated in tumor progression and resistance to EGFR inhibitors. The aim of this study was to investigate the effects of combining the mTOR inhibitor temsirolimus (Tem) with the anti‐EGFR agent cetuximab (Cet) and conventional chemotherapeutic drugs (cisplatin and fluorouracil (C/F)) on an orthotopic model of HNSCC. Study Design: Preclinical in vivo study. Methods: We evaluated the anti‐tumor efficacy (measured tumor volume) of Tem, Cet, and C/F, administered alone or in combination. Investigations were performed using a human HNSCC cell line, CAL33, injected into the mouth floor of nude mice. Results: As compared with the control, the combination of Tem and Cet led to the highest tumor inhibition and induced almost complete tumor growth arrest ( P = 0.001). Tem significantly enhanced the impact of the Cet‐C/F combination on tumor growth ( P < 0.001). The highest inhibitory effects of treatments on cell proliferation (Ki67 labeling), MAPK (pP42/44 labeling), and PI3K/AKT/mTOR (pS6R labeling) signaling pathways were found with the Tem‐Cet association. Conclusion: In this orthotopic HNSCC model, the combination of Tem with Cet produced synergistic effects on tumor growth. These results were corroborated by a strong inhibition of both MAPK and PI3K‐mTOR signaling pathways. Level of Evidence: N/A. Laryngoscope, 126:E156–E163, 2016